Enhance the User Interface Design of the booking application at Rana Photo Studio by applying the User-Centered Design (UCD) method - Nuria, Putri; Septiana E.P, Ellyv; Safitri, Ayin Dewi; Solehatin, Solehatin (ULTIMA InfoSys, 2024)
The goal of this research is to create an interface design for a photo studio booking application. The User Centered Design (UCD) method will be used to prioritize the user interface and user experience. The success of the UI/UX design will be validated by involving users directly throughout the development cycle using UCD principles. This will include collecting feedback and continuously improving the design based on user input. The research conducted in this study involved the User Created Design method, which utilized an interactive user interface to enable easy booking of studios with a convenient and efficient booking system for customers to use anywhere and anytime. Online booking overcomes the challenge of scheduling difficulties. The information system is treated with accuracy and appropriateness to ensure direct user accessibility. The research was conducted in three stages, starting with the initial stage of data collection and literature study, followed by the UCD Method Development stage, where the method was developed and solutions to early-stage problems were sought. The final stage included a decision-making process based on the conclusions drawn from the insights of five audiences. Through the application of the User Centered Design method, this research has successfully developed a UI/UX design that meticulously takes into account the users' needs during the studio photo booking process. The evaluation results derived from user feedback has increased the system's effectiveness, provided an intuitive and delightful user experience, and ensured optimal user engagement throughout the entire ordering journey. Based on the evaluation results of user responses, it can be concluded that the system has been successful in providing an intuitive and satisfying experience. Users have given positive feedback regarding the effectiveness of the user interface (UI) and user experience (UX), which indicates significant improvements in system navigation and the ease of the ordering process. A deep understanding of user needs, along with continuous iteration based on feedback, has resulted in a positive experience and ensured a high level of satisfaction with the use of this studio photo booking system. Keywords: Information System, UI/UX, User-Centered Design (UCD), Online Booking.